Hamstring Muscle Tightness and Chronic Low Back Pain an Analytical Study on General Population - Farwah Batool, Qurba Kiran, Humera Mubashar, Masooma Gull, Amena Batool, Sana Ashraf, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The low back is a common disorder prevalent in general population having an association with hamstring tightness which needs to be addressed while its prevention or management strategies. The objective was to find if there is any link between CLBP severity and hamstring muscle tightness. Methods: A cross-sectional analytical study was carried out on 160 patients with persistent LBP, fulfilling the criteria of the study. After ethical approval, data was gathered from Ayesha Sadiqa Hospital Lahore. The low back pain disability index was measured using Oswestry Disability Index and Hamstring tightness was evaluated using clinical Active knee extension test. The data were analysed using SPSS V.23 and Chi square was used to determine association between outcomes. Result: There were 160 participants, among them 114 (71.25%) experiencing hamstring tightness and 46 (28.75%) not having hamstring tightness. Females had a greater prevalence than males. The findings suggest that hamstring tightness affected 61% patients with moderate impairment. There was an association of hamstring tightness with disability Index among the participants at p Value <.01. Conclusion: In subjects with back pain, hamstring tightness has an association with activities of daily life other than sexual preferences, community interactions, and journey. The chronic low back pain has direct association with hamstring muscle tightness in our target population. Keywords: Association, Chronic Low Back Pain, Hamstring Muscle, Tightness